The Journal Selection Problem in a University Library System - Kraft, D. H.; Hill, T. W. (Management Science, 1973)
The problem of selecting which journals to acquire in order to best satisfy library objectives is examined and modeled as a zero-one linear programming problem This is done using an objective function based on expected usage as a measure of journal worth and on cost constraints which account for the scarcity of capital. A dynamic programming algorithm is used to break down the larger problem into smaller sub-problems and to generate a feasible solution. Special cases where the solution is optimal are presented and discussed in terms of their implications for the library. An example problem is presented to illustrate the algorithm.